RESILIENSI DAN KESIAPSIAGAAN PERAWATDALAM MENGHADAPI BENCANA - Siti Luthfiana Hasena (2023)
Adequate resilience and preparedness are needed by nurses considering that nurses are the largest number of health workers & have an important role in disaster management. Inadequate resilience & preparedness of nurses will have an impact on increasing the number of victims, not meeting the needs of victims & the death of health workers. The purpose of this study was to find out the relationship between resilience & disaster preparedness for nurses at the research location hospital. The research method used is cross sectional by using the Chi Square test with 260 samples obtained by the quota sampling method. The research instrument used is a questionnaire that has been tested for validity & reliability. The results of this study indicate that there is a significant relationship between resilience & disaster preparedness with a p-value of 0.00 (p <0.05), while the characteristics of the respondents; gender (p=0.066), education level (p=0.774), age (p=0.327), work experience (p=0.432), employment status (p=0.218) & marital status (p=0.135) indicated that there was no significant relationship with disaster preparedness. This research is expected to provide an overview regarding the extent to which the resilience & individual readiness of a nurse in disaster area so that the role of nurses in disaster conditions more effectively.